مسارات التأويل النص وتحولات السياق المعرفي - ولد متالي لمرابط أحمد, محمدو (قــــــراءات, 2019)
يتناول هذا البحث موضوع«التأويل»، مقدمًا جانبامهما من أطروحات بعض المفكرين والنقاد –عربيا وغربيا- ممن قدموا تصورات وفرضيات محددة في هذا السياق. كما يثير جزءامن الإشكاليات الكبرى التي ظلت متداولة في سياق قراءة النصوص، وما تفرضه على القارئ من ضرورة وضوح المنطلقات، والبحث الدائب عن بهاء المعنى الذي يختفي خلف حجاب اللغة، مما يحتمعلى المؤول الوعي بلعبة الخفاء والتجلي التي يمارسها جلّ النصوص.من هنا يروم هذا البحث تقديم مقاربة علمية لمسار التأويل، واستعراض جهود أبرز المفكرين القدماء والمحدثين في التنظير له وتحديد أسسه ومبادئه.   Research Summary:   This research deals with the subject of interpretation.  It looks at an important aspect of the perceptions and assumptions that were put forward by some Arab and western thinkers and critics. This research also looks at part of the problems faced in the context of reading and understanding texts, which forces the reader to continually search for meaning hidden behind the veil of language. This makes it imperative for the interpreter to be aware of the game of hide and seek in most of texts. From here this research aims to provide an empirical approach to draw closer the different methods of interpretation. It also reviews the efforts of some of the most influential thinkers both in ancient and modern in his theorizing and determining the foundations and principles of interpretation.